Ideological Control and Power Dynamics in Kazuo Ishiguro’s Never Let Me Go: A Critical Discourse Analysis through a Marxist Lens - Khattak, Junaid Ahmed; Yunita Sari Adelina; Talha Idrees (English Lecturers and Teachers Association (ELTA), 2025)
Never Let Me Go by Kazuo Ishiguro is a widely acclaimed novel that explores themes of identity, conformity, and social control. While numerous studies have examined the novel through various literary and critical lenses, there is a notable lack of research analyzing it through the Marxist postulates of power dynamics, and ideological control. This study addresses this gap by applying Van Dijk’s Critical Discourse Analysis (CDA) to investigate how the novel portrays power dynamics and ideological control resulting in oppression of characters and the internalization of ideology. This qualitative research examines Never Let Me Go by Kazuo Ishiguro through the Marxist postulates of power dynamics, and ideological control, utilizing Van Dijk’s Critical Discourse Analysis (CDA) as an analytical model. By applying Van Dijk’s CDA framework, the research reveals how the clones, as a marginalized underclass, internalize their exploitation, reinforcing the hegemonic structures that govern them. The findings of this study contributes to Marxist literary criticism and discourse analysis, offering new insights into the intersection of language, power, and ideology in Ishiguro’s dystopian narrative. Keywords : Never Let Me Go, Critical Discourse Analysis, Marxist Criticism, Ideological